Anak Yang Takut Akan Tuhan Beroleh Harapan Masa Depan Yang Indah Amsal 23:15-18 - Ivana Lidya Hasibuan; Suang Manik; Herdiana Boru Hombing (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In Proverbs 23:15-18, we are told that children who fear the Lord will have hope for a bright future. This means that when someone has a healthy fear of God, they will live in a righteous and wise way. They will respect their parents and follow God's teachings, which in turn will lead them in a good direction. A child who always listens to his parents' advice and follows their religious teachings. The child will grow up to be a responsible, honest and loving person. They will have confidence that their future will be good because they live according to the values ​​instilled by God. What is written in this verse is the importance of having a healthy fear of God in shaping a bright and hopeful future.